2009
DOI: 10.4049/jimmunol.0802400
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Amount of the Common γ-Chain Influences Spontaneous or Induced Cell Proliferation

Abstract: Mutations of the IL2RG encoding the common ␥-chain (␥ c ) lead to the X-linked SCID disease. Gene correction through ex vivo retroviral transduction restored the immunological impairment in the most of treated patients, although lymphoproliferative events occurred in five of them. Even though in two cases it was clearly documented an insertional mutagenesis in LMO2, it is conceivable that ␥ c could have a role per se in malignant lymphoproliferation. The ␥ c is a shared cytokine receptor subunit, involved also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…26,27 Although insertional oncogene activation was reported in three of the leukemic cases it has also been demonstrated that overexpression of the common c chain induces cellular proliferation and may have contributed to the T lymphocyte clonal outgrowth. [26][27][28] Tighter regulation of the common c chain gene may thus reduce the risk of oncogenesis resulting from aberrant overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Although insertional oncogene activation was reported in three of the leukemic cases it has also been demonstrated that overexpression of the common c chain induces cellular proliferation and may have contributed to the T lymphocyte clonal outgrowth. [26][27][28] Tighter regulation of the common c chain gene may thus reduce the risk of oncogenesis resulting from aberrant overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Although insertional activation of the LMO2 oncogene was reported in three of the leukemic cases, overexpression of the common g chain also likely contributed to these adverse events (HaceinBey-Abina et al, 2008;Howe et al, 2008). It has subsequently been demonstrated that overexpression of the common g chain induces cellular proliferation that may have ultimately been responsible for the T lymphocyte clonal outgrowth (Amorosi et al, 2009).…”
Section: Multhaup Et Almentioning
confidence: 99%
“…However, the effects of adiponectin in promoting an MM-permissive microenvironment may be multifactorial and additionally include effects on the recruitment of innate immune cells, such as macrophages. 5 These elegant studies suggest a novel concept that the expression of adipokines such as adiponectin in the tumor microenvironment may regulate the permissive state of the marrow microenvironment to MM growth.…”
Section: Madhav V Dhodapkar Yale Universitymentioning
confidence: 99%
“…Gamma chain and T-cell development, the role of several ␥-related cytokines in T-cell differentiation and functions, molecular therapy and immune reconstitution through gene transduction, and the general role of the molecule in cell-cycle progression and tumorigenesis are only a few examples that highlight the importance of studies of primary immunodeficiencies (PIDs) that go far beyond the understanding of the cause of a disease. 4,5 Very often, studies in this field highlight shared aspects, which also help unravel It is not surprising that the greater the number of the distinct immunologic disorders, the greater the diversity of presenting signs. Much time elapsed from the paradigm that a severe PID should have been ruled out if the patient had recovered from an infection by the time expected.…”
mentioning
confidence: 99%